Representation of Javanese Women Symbolic Violence in Serial Movie Gadis Kretek - Andari, Trias Widha; Utami, Athika Dwi Wiji (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The practice of symbolic violence is common in the social dynamics of society. Symbolic violence, according Pierre Bourdieu, has different meaning from actual violence. Symbolic violence is caused by the subordination of an individual to an individual or other group that dominates. The analysis of symbolic violence is not in spite of the concept of habitus, arena, and the capital that was presented by Bourdieu. The study is discussed about symbolic violence to women who were represented by Serial Movie Gadis Kretek. This research uses a qualitative approach with a method of discourses analysis. Serial Movie Gadis Kretek main character, Dasiyah, is a representation of symbolic violence carried out in the social order of society. The result of this research is symbolic violence, in Serial Movie Gadis Kretek, starting from the smallest organization unit in the social structure, main family. Symbolic violence is prone in traditional patriarchal culture, believed by peoples, by means of the dominant role of men toward women.